Purification and molecular cloning of the scaffold attachment factor B (SAF-B), a novel human nuclear protein that specifically binds to S/MAR-DNA. - Renz, A (1996)
We have purified to near homogeneity a novel nuclear protein from HeLa cells, that specifically binds to scaffold or matrix attachment region DNA elements (S/MAR DNA). The protein, designated SAF-B for scaffold attachment factor B, is an abundant component of chromatin, but not of the nuclear matrix and is expressed in all human tissues investigated. Antibodies against the purified protein were raised in rabbit and used to isolate the complete cDNA encoding SAF-B by immunoscreening. As predicted from the cDNA sequence, SAF-B contains 849 amino acids (96 696 Da), without significant homology to any known protein. SAF-B is rich in charged residues, leading to an aberrant migration on SDS gels, and has two putative bipartite nuclear localisation signals.